ANALYSIS OF FUNDS FROM THE STATE BUDGET TO SCIENTIFIC ORGANIZATIONS FOR THE FIGHT AGAINST CORONAVIRUS INFECTION "COVID-19" - Sh.I. Otajonov; Sh.E. Ibragimov (International Journal on Economics, Finance and Sustainable Development, 2021)
This article provides an analysis of the funds allocated from the state budget for scientific research and studies related to the coronavirus pandemic and the analysis of scientific research carried out by scientific organizations.